2022
DOI: 10.1063/5.0100170
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical understanding on all-solid frustrated Lewis pair sites of C2N anchored by single metal atom

Abstract: Designing all-solid heterogeneous catalysts with frustrated Lewis pairs (FLPs) has aroused great attentions recently because of its appealing low dissociation energy for H2 molecule and thus a promotion of hydrogenation reaction is expected. The sterically encumbered Lewis acid (metal site) and base (nitrogen site) in the cavity of single transition metal atom doped M/C2N sheet makes it potential candidate with FLP, while a comprehensive understanding of its intrinsic property and reactivity is still required.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…The geometric structures of transition states agree with the characteristic shape of the acid−H−H−base fragments reported in previous studies. 19,44,45,75 The hydrogen atom near the B atom at both IS and TS has negative atomic charges, while the hydrogen atom near the N atom possesses positive charges. In addition, Figure 5 shows electron density increases notably between the B atom and the hydrogen adjacent to the B atom but decreases apparently around the hydrogen adjacent to the N atom.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The geometric structures of transition states agree with the characteristic shape of the acid−H−H−base fragments reported in previous studies. 19,44,45,75 The hydrogen atom near the B atom at both IS and TS has negative atomic charges, while the hydrogen atom near the N atom possesses positive charges. In addition, Figure 5 shows electron density increases notably between the B atom and the hydrogen adjacent to the B atom but decreases apparently around the hydrogen adjacent to the N atom.…”
Section: Resultsmentioning
confidence: 99%
“…As far as our knowledge, the first case of constructing heterogeneous FLPs is reported by Sautet and co-workers, where the nonadjacent Al···O pairs on the γ-alumina surface with both strong acidity and basicity are highly active for the heterolytic splitting of both H 2 and CH 4 . , Subsequently, Singh and co-workers reported that the In···O FLPs constructed on hydroxylated indium oxide surface with oxygen vacancies can effectively catalyze H 2 dissociation and following CO 2 hydrogenation. Recently, solid FLPs constructed by regulation of surface oxygen vacancies on reduced CeO 2 surfaces were proposed for hydrogen dissociation and methane conversion. ,, The enhanced FLP acidity and basicity together with the elongated distance of Ce···O pairs contribute to the high activity of the solid FLPs for hydrogen dissociation and acetylene hydrogenation . Besides oxide surfaces, designing heterogeneous FLPs has been proved by various strategies and materials, , such as functionalizing metal–organic framework (MOF), ,, adsorbing molecules on solid surfaces and doping two-dimensional materials. , Despite these significant advances in designing heterogeneous FLPs, metal elements are still indispensable for the construction of heterogeneous FLPs, which deviates from the initial metal-free concept of FLP catalysis . Therefore, it is imperative to develop metal-free heterogeneous FLPs which retain the high activity for hydrogen dissociation and match the original conception of FLPs as metal-free catalysts.…”
Section: Introductionmentioning
confidence: 99%